1979
DOI: 10.1111/j.1365-2389.1979.tb00982.x
|View full text |Cite
|
Sign up to set email alerts
|

THE pH DEPENDENCE OF THE SURFACE CONCENTRATIONS OF CALCIUM AND PHOSPHORUS ON HYDROXYAPATITE IN AQUEOUS solUTIONS

Abstract: A radioisotope dilution technique was used to measure the surface concentrations of Ca and P on hydroxyapatite equilibrated at pH values ranging from 5.19 to 8.81. The concentrations were rarely equal to those calculated for a stoichiometric surface. In general the &molar surface Ca/P increased from a value less than the stoichiometric figure of 1.67 at low pH values to a value greater than 1.67 at high pH values. The solution Ca/P showed the opposite trend with pH. The deviations of the surface concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…1), Secondly, the Ca:P ratio decreases towards values similar to CaP minerals (Fig. 3) with the highest P extractions (Bell and Mika, 1979;Lindsay, 1979;Nezat et al, 2008). Thirdly, the cumulative P released by the two methods was similar.…”
Section: P Extractionmentioning
confidence: 81%
“…1), Secondly, the Ca:P ratio decreases towards values similar to CaP minerals (Fig. 3) with the highest P extractions (Bell and Mika, 1979;Lindsay, 1979;Nezat et al, 2008). Thirdly, the cumulative P released by the two methods was similar.…”
Section: P Extractionmentioning
confidence: 81%
“…With these minerals the plateau F/Ca level never reached 0.2, suggesting that a F-enriched FHAp rather than pure fluorapatitc pre cipitates during dissolution. It is concluded that a high-F FHAp mineral would best serve as an apatitic plaque reservoir of F.During the partial dissolution of hydroxyapatite (HAp) the ratio of calcium (Ca) and phosphate (P) in solution is often found to deviate from the overall ratio in the solid phase [Bell ct al.. 1978], This non-stoichiometry ofCaand P release is most pronounced during the initial stages of dis solution and has been variously ascribed to the initial ad sorption of Ca or P on the crystal surfaces [Bell and Mika, 1979], to abnormalities in the surface unit cells [Smith et al, 1974] and to re-precipitation phenomena [LaMer, 1962;Mayer et al, 1988], Fluorhydroxyapatite (FHAp), a mineral in which a varying proportion of the OH ions is replaced by F ions, has been little studied in this respect. During single equilibrations in acid, the concentration of F in solution is sometimes lower than expected, i.e., the F/Ca ratio in solu…”
mentioning
confidence: 99%
“…1975] attain congruent dissolution. However, differ ing explanations have been given; abnormalities in the sur face unit cells of the crystals [Smith et al, 1974], initial ad sorption of excess Ca or P on the crystal surface [Bell and Mika, 1979], preferential dissolution of the more soluble mineral constituents, and a re-precipitation phenomenon which eventually ceases.…”
Section: Discussionmentioning
confidence: 99%
“…The pH usually rose during the equilibration period and this would be expected to favour adsorption of Ca, i.e. its remov al from solution in relation to P [Bell and Mika, 1979], How ever, the reverse occurred. No doubt adsorption did play some role in determining solution Ca and P values, as our solid/solution ratio was very high, but it could not override the effects of other processes.…”
Section: Discussionmentioning
confidence: 99%